Comparative analysis of gut symbionts in Tribolium castaneum (Coleoptera: Tenebrionidae) and their dietary substrate, sauce-flavored Daqu - Jun Lü; Shan Xu; Can Teng; Rujia Huang; Guiqin Xiong; Qin Cheng (Frontiers in Insect Science)
Tribolium castaneum (red flour beetle), a major pest infesting stored sauce-flavored Daqu (SFD), causes significant economic losses in the sauce-flavored liquor industry. This study analyzed microbial interactions between SFD and T. castaneum (adults and larvae) using 16S rDNA and ITS sequencing. T. castaneum guts primarily hosted Bacteroidota (44.7% adults, 50.9% larvae) and Proteobacteria, contrasting SFD’s Firmicutes-dominated community (89.3%), featuring Oceanobacillus (31.7%) and Bacillus (11.2%). Fungal communities across groups were Ascomycota-rich (90%), with Aspergillus (86%) as core, while larvae uniquely harbored Lichtheimia (5.5%). Larvae shared more bacterial taxa with SFD (5 genera vs. 3 in adults), yet high-abundance SFD bacteria (e.g., Weissella) were scarce in guts (0.6%) and vice versa. Fungal source tracking revealed SFD contributed 89–94% of gut fungi, vastly exceeding bacterial inputs (2.8–5%). Shared bacterial ASVs (n=58) exhibited functional divergence: carbohydrate metabolism dominated in SFD, whereas insect-associated ASVs enriched drug resistance genes. Findings suggest T. castaneum selectively colonizes SFD bacteria (e.g., Bacillus, Oceanobacillus) while proportionally acquiring fungi (e.g., Aspergillus) via dietary transmission. These microbes may act as a gut “seed bank” or host-selected symbionts, warranting further validation to clarify their ecological roles and inform microbially-based pest control strategies.